Optimization of three key ejector geometries under fixed and varied operating conditions: A numerical study. (5th July 2022) - Li, Ruixin; Yan, Jia; Reddick, Christopher
Highlights: Relative sensitivity of ejector performance to three key geometries was evaluated. Effect of six optimization sequences of three key geometries was analyzed. Ejector performance under varied working conditions was discussed. Re-optimization of three geometries under four typical conditions was conducted. Abstract: In this paper, as for an ejector utilized in a carbon capture system, by using CFD simulation, its three key geometries such as length of constant-pressure mixing chamber (XL3), length and diameter of constant-area mixing chamber (XL5 and D5) were first optimized individually. Then, the relative sensitivity of ejector performance to the three geometries was identified. Next, the effect of six optimization sequences (S1: XL3 → D5 → XL5, S2: XL3 → XL5 → D5, S3: XL5 → D5 → XL3, S4: XL5 → XL3 → D5, S5: D5 → XL3 → XL5, S6: D5 → XL5 → XL3) of the three geometries on entrainment ratio (ER) was evaluated. And then, the ER under varied working conditions was analyzed. Finally, four typical working conditions were selected for doing re-optimization to check whether the ejector performance can be significantly improved and how big difference of the optimized geometries with re-optimization can be generated. The results showed that: (1) the relative sensitivity of ER to D5 is greater than XL3, and that to XL5 is the least; (2) Among six optimization sequences of three geometries, S2 offers the best ejector performance, both S5 and S6 generate the equal and lowest ER; (3) The change of ER with the primary flow pressure is largely related to the back pressure; (4) Re-optimization under four typical operating conditions can improve ejector performance by 4.3% ∼ 128.8%, and optimum D5 and XL3 increases evidently as compared to that without re-optimization. The research results would enhance the application of ejector in carbon capture and relevant chemical fields.